Surveillance of Circulating Bordetella pertussis Strains in Europe during 1998 to 2015 - Barkoff AM (AMER SOC MICROBIOLOGY, 2022)
One reason for increased pertussis incidence is the adaptation of Bordetella pertussis to vaccine-induced immunity by modulating its genomic structure. This study, EUpert IV, includes 265 isolates collected from nine European countries during 2012 to 2015 (n = 265) and compares the results to previous EUpert I to III studies (1998 to 2009). The analyses included genotyping, serotyping, pulsed-field gel electrophoresis (PFGE), and multilocus variable-number tandem-repeat analysis (MLVA). Genotyping results showed only small variations among the common virulence genes of B. pertussis. The frequencies of serotypes Fim2 and Fim3 varied among the four collections. Genomic analyses showed that MLVA type 27 increased to 80% between the periods of 1998 to 2001 and 2012 to 2015. Two PFGE profiles, BpSR3 (29.4%) and BpSR10 (27.2%), constituted more than 50% of the circulating isolates in the present collection. Our study indicates that the European B. pertussis population is changing and became more homogenous after the introduction of acellular pertussis vaccines.